Small firms, R&D, technology and innovation in the UK a literature review - Hoffman, Kurt (Technovation)
This work offers a guide to the literature on small and medium-sized enterprises (SMEs) and their innovative activities. Gaps and deficiencies in the literature are indicated, as are areas for future research.